2019
DOI: 10.1088/1757-899x/566/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of aggregate gradation on the fresh and hardened concrete properties

Abstract: This experimental study is focused on the aggregate gradation impact on the properties of fresh and hardened concrete. For the experiment, 9 mix design were prepared with the constant content of cement, effective water, plasticizer and aggregate. The variable factor is represented by different proportions of 4 fraction (0/0.7, 0/4, 4/8, 8/16). Consistency by slump and flow table in time, compressive strength, water absorption and density were measured. Some significant differences were observed. Consistency by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Excluding samples NZ7.5_0.3 and NZ7.5_0.4, oven-dried samples achieved significant higher values (increase from 10.5 rel.% up to 48.9 rel.%) of compressive strength on day 28 day, as those in ssd state. This has been proven in our previous studies [ 21 , 104 ].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Excluding samples NZ7.5_0.3 and NZ7.5_0.4, oven-dried samples achieved significant higher values (increase from 10.5 rel.% up to 48.9 rel.%) of compressive strength on day 28 day, as those in ssd state. This has been proven in our previous studies [ 21 , 104 ].…”
Section: Resultssupporting
confidence: 82%
“…With increase in cement paste amount of same w/c, the volume of the pores increases, thus increasing porosity and permeability [ 19 ]. The main factor of cement paste quantity is the aggregate (mainly its granularity and grain shape) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. This is due to voids that are created between grains that have to be fulfilled by cement paste.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, manufactured sand is a byproduct of the coarse aggregate production that has been successfully used for making concrete. Although it has been concluded that angular shape of fine aggregates increases compressive strength in comparison with rounded shapes [2][3][4], the detrimental impact on fresh properties is the main limiting factor to increase its use. However, increasing the content of manufactured sand in new concrete involves environmental benefits since lower quantities of natural sand would be required.…”
Section: Introductionmentioning
confidence: 99%